EO9 (Apaziquone): from the clinic to the laboratory and back again - Phillips, Roger M; Hendriks, Hans R; Peters, Godefridus J (British journal of pharmacology, 2013)
EO9 (Apaziquone) is a bioreductive drug that has a chequered history. It underwent clinical trial but failed to show activity in phase II clinical trials when administered i.v. Poor drug delivery to tumours caused by a combination of rapid pharmacokinetic elimination and poor penetration through avascular tissue were the major factors responsible for EO9's poor efficacy. Based upon an understanding of why EO9 failed, a further clinical trial against patients with superficial transitional cell carcinoma of the bladder was conducted. The rationale for this was that intravesical administration directly into the bladder would circumvent the drug delivery problem, and any drug reaching the blood supply would be rapidly cleared thereby reducing the risk of systemic exposure. EO9 was well tolerated, and clinical activity against marker lesions was recorded in both phase I and II clinical trials. This article charts the pharmacological history of EO9 and discusses the potential implications that ‘the EO9 story’ has for the development of other loco‐regional therapies.